2020
DOI: 10.4103/aian.aian_264_19
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug Prices, Availability and Affordability in a Resource-Limited Setting

Abstract: Background: The availability and affordability of antiepileptic drugs (AEDs) are critical to the success of public health initiatives enabling care for people with epilepsy in the community. Objective: To pilot survey the availability and affordability of AEDs in the community. Methods: Field workers used standard WHO–Health Action International approaches and collected data on the availability of, and maximum retail prices of originator bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 25 publications
(13 reference statements)
2
22
0
Order By: Relevance
“…The higher cost of newer AEDs such as lamotrigine and levetiracetam, their limited availability in the public distribution system, and lack of familiarity with updated guidelines of the care providers are important barriers to their wider use. 27 The strategies for meeting the cost of chronic medical conditions are heavily influenced by several socioeconomic and administrative factors. 28 Lamotrigine, levetiracetam, and other newer AEDs are expensive and are not widely available in public hospitals, 29 although they are included in the essential drug list in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher cost of newer AEDs such as lamotrigine and levetiracetam, their limited availability in the public distribution system, and lack of familiarity with updated guidelines of the care providers are important barriers to their wider use. 27 The strategies for meeting the cost of chronic medical conditions are heavily influenced by several socioeconomic and administrative factors. 28 Lamotrigine, levetiracetam, and other newer AEDs are expensive and are not widely available in public hospitals, 29 although they are included in the essential drug list in India.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 10% of women were tried on lamotrigine or levetiracetam before switching to VPA. The higher cost of newer AEDs such as lamotrigine and levetiracetam, their limited availability in the public distribution system, and lack of familiarity with updated guidelines of the care providers are important barriers to their wider use 27 . The strategies for meeting the cost of chronic medical conditions are heavily influenced by several socioeconomic and administrative factors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Singh et al . [ 5 ] the authors have found major problems of availability, affordability, and other aspects for the management of PWE.…”
mentioning
confidence: 99%
“…have surveyed the availability and affordability of antiepileptic drugs (AEDs) in the community at Ludhiana city, in Punjab state in northwest India. [ 5 ] They have presented data on the availability and maximum retail prices of originator brands and least price generics of AEDs in 46 randomly selected public ( n = 29), private ( n = 8), and charitable ( n = 9) pharmacy outlets. The data point toward a gross deficiency in the availability of AEDs in most places.…”
mentioning
confidence: 99%